Nilai Keberanian Lelaki Dalam Naskah Mursada dan Implikasinya Terhadap Peran Lelaki dalam Keluarga - Sari, Dian Kartika; Sulistyaningsih, Niken (Jurnal Online Baradha, 2023)
The value of courage is one of the good moral values possessed by humans. The value of courage is contained in the Mursada Manuscript. The value of courage is very important for a man to face all the problems faced by his family. This study aims to describe the value of courage and analyze the implications of the value of courage in the Mursada Manuscript with the role of men in the family. The research data source is the Mursada Manuscript with 158 pages. Data collection techniques in this study were carried out by library research. The data analysis technique used is data reduction, presentation and conclusion. This article uses the theory of philology and dynamic structuralism theory by Mukkarovsky. The results of this study are that the Mursada Manuscript contains the value of courage possessed by the male characters in the Mursada Manuscript which include the value of courage to take risks, the value of courage to fight for the truth, the value of courage to save others, the value of courage to fight enemies and the value of courage to make decisions. The value of courage must be owned by men in the family to carry out their roles to be leaders, protectors and decision makers on various problems in their families.Keywords : Courage, male role, Naskah MursadaNilai keberanian merupakan salah satu nilai moral baik yang dimiliki oleh manusia. Nilai keberanian terkandung dalam Naskah Mursada. Nilai keberanian sanget penting dimiliki oleh seorang lelaki guna menghadapi segala permasalahan yang dihadapi keluarganya. Penelitian ini bertujuan untuk mendeskripsikan nilai keberanian dan menganalisis implikasi nilai keberanian dalam Naskah Mursada dengan peran lelaki dalamkeluarga. Dengan sumber data penelitian berupa Naskah Mursada dengan 158 halaman. Teknik pengumpulan data pada penelitian ini dilakukan dengan studi pustaka. Teknik analisis data yang digunakan ialah reduksi data, penyajian dan penarikan kesimpulan. Artikel ini menggunakan teori filologi dan teori strukturalisme dinamik oleh Mukkarovsky. Hasil dari penelitian ini ialah Naskah Mursada mengandung nilai keberanian yang dimiliki oleh tokoh lelaki dalam Naskah Mursada diantaranya ialah nilai keberanian mengambil resiko, nilai keberanian memerjuangkan kebenaran, nilai keberanian menyelamatkan orang lain, nilai keberanian melawan musuh dan nilai keberanian mengambil keputusan. Nilai keberanian tersebut harus dimiliki oleh lelaki dalam keluarga untuk menjalankan perannya untuk menjadi pemimpin, pelindung dan pengambil keputusan pada berbagai permasalahan dalam keluarganya.Kata kunci : Keberanian, Peran lelaki. Naskah Mursada